"Most Prized Possessions": Photography as Living Relationships within the End-of-Life Care of Newborns. (October 2014) - Martel, Sara L.; Ives-Baine, Lori
This article reports findings from a phenomenological inquiry into how parents experience End-of-Life (EOL) photography around the death of their newborn in the neonatal intensive care unit (NICU) and in their lives beyond the hospital. The study involved semi-structured interviews with 10 parents who had experienced the death of their newborn within the last five years in the same NICU setting. All parents had participated in EOL photography, having photos taken by nurses, by themselves, and/or by volunteer professional photographers. Through an Interpretive Phenomenological Analysis, the theme of "living relationships" emerged, revealing the photography as valued more than for the photos as "mementos, " but further as an activity grounding relationships and fostering interaction between families, newborns, and care-providers; these findings provide insight into how parents came to see their EOL photos as "prized possessions." The article is concluded with a discussion on a Model for Photographing Living Relationships.